About structure content and purpose of the National atlas of Uzbekistan (Journal of Geography and Environmental Management, 2016)
This article dedicated to the development of the concept of the National atlas, its principles of development, content, structure and purpose. Justifiedneedsandnecessityofitsdevelopment
Keywords: Atlas Cartography; concept of National atlas